A comparison of non‐invasive methods of measuring body composition in patients with heart failure: a report from SICA‐HF. (3rd July 2021) - Shah, Parin; Abel, Alexandra A.I.; Boyalla, Vennela; Pellicori, Pierpaolo; Kallvikbacka‐Bennett, Anna; Sze, Shirley; Cleland, John G.F.; Clark, Andrew L.
Abstract: Background: Cachexia is common in patients with chronic heart failure and is associated with poor prognosis. How best to measure body composition is not clear. Methods and results: We characterized body composition in 120 patients with chronic heart failure: mean (SD) age 70 (10) years, left ventricular ejection fraction 44 (10) %, and median (Q1–Q3) N‐terminal pro B‐type natriuretic peptide 845 (355–1368) ng/L. We measured body composition using dual‐energy X‐ray absorptiometry (DEXA) and a multi‐frequency bioelectrical impedance analysis (BIA) device (Tanita BIA MC‐180MA). Mean (SD) fat mass (FM) was 27.2 (11.7) kg by BIA and 32.3 (12.2) kg by DEXA (mean difference −5.1 kg, 95% limits of agreement: −11.7, 1.5; 4% of values outside limit of agreement); mean (SD) lean mass (LM) was 56.6 (10.9) kg by BIA and 51.1 (9.9) kg by DEXA (mean difference 5.5 kg, 95% limits of agreement: −1.3, 12.3; 6% of values outside limit of agreement); and mean (SD) bone mass (BM) was 3.0 (0.5) kg by BIA and 2.8 (0.6) kg by DEXA (mean difference 0.2 kg, 95% limits of agreement: −0.5, 0.8; 5% of values outside limit of agreement). There was a close correlation between DEXA and BIA for both LM and FM (LM: r  = 0.95, P  < 0.001; FM: r  = 0.96, P  < 0.001) but less so for BM ( r  = 0.84, P  < 0.001). Both DEXA and BIA body composition measurements correlated well with other measures of body size (body mass index, hip circumference, and waist circumference). Conclusions: There are differences in the measurements of FM, LM, and BM between the two techniques, which should not be used interchangeably.